Circannual variation of efficacy outcomes in patients with newly diagnosed metastatic colorectal cancer and treated with first-line chemotherapy. (26th November 2015) - Tampellini, M.; Polverari, R. S.; Ottone, A.; Alabiso, I.; Baratelli, C.; Bitossi, R.; Brizzi, M. P.; Leone, F.; Forti, L.; Bertona, E.; Racca, P.; Mecca, C.; et al.
Abstract : Seasonal variation of baseline diagnosis (or clinical suspect) of stage I–III colorectal cancer patients has been repeatedly reported as an independent variable influencing overall survival. However, data are conflicting and no information is available about such a rhythm in advanced stage patients. To test whether a circannual rhythm of efficacy outcomes can be detected in this setting, we collected data about response rate (RR), progression-free survival (PFS), and overall survival (OS) to first-line chemotherapy of 1610 newly diagnosed metastatic patients treated at four independent centers. Responses to first-line chemotherapy were available for 1495 patients. A strong circannual rhythm in RR was evident, with the higher proportion of responding patients in the subgroup diagnosed in January (acrophase). At the time of data cutoff, 1322 patients progressed and 986 died, with median PFS and OS of 11 and 25.6 months, respectively. A circannual rhythmicity of the proportion of patients progressing at 6 months and surviving at 1 year was demonstrated, with acrophases located both in winter (February and January, respectively), similar to what reported for RR. Several interpretations about the genesis of this cyclic variation could be claimed: the rhythm in sunlight exposure and, as a consequence, of vitamin D serum levels and folate degradation, the variability in toxic effect intensity of chemotherapy, and the rhythm in the biological behavior of tumor cells. This observation is worth of further investigation both in preclinical and in clinical settings in order to better elucidate the underlying mechanisms.